Multi-agent Oriented Programming and Intelligent Environments - Boissier, Olivier (2013 19th International Conference on Control Systems and Computer Science, 2013)
These last years, the multi-agent domain has proposed several proposals for the development of decentralised and open systems given birth to agent-oriented, environment-oriented, interaction-oriented or organisation-oriented programming approaches. In this paper, instead of privileging one dimension, we propose a seamless integration of these programming approaches into what we call "multi-agent oriented programming". We discuss how this approach brings the full potential of multi-agent systems as a programming paradigm to be used in the development of Intelligent Environments. We illustrate this with some applications and discuss how it opens interesting perspectives for ambient computing.